Tidal Dwarf Galaxies and Missing Baryons - Frederic Bournaud (Advances in Astronomy)
Tidal dwarf galaxies form during the interaction, collision, or merger of massive spiral galaxies. They can resemble “normal” dwarf galaxies in terms of mass, size, and become dwarf satellites orbiting around their massive progenitor. They nevertheless keep some signatures from their origin, making them interesting targets for cosmological studies. In particular, they should be free from dark matter from a spheroidal halo. Flat rotation curves and high dynamical masses may then indicate the presence of an unseen component, and constrain the properties of the “missing baryons,” known to exist but not directly observed. The number of dwarf galaxies in the Universe is another cosmological problem for which it is important to ascertain if tidal dwarf galaxies formed frequently at high redshift, when the merger rate was high, and many of them survived until today. In this paper, “dark matter” is used to refer to the nonbaryonic matter, mostly located in large dark halos, that is, CDM in the standard paradigm, and “missing baryons” or “dark baryons” is used to refer to the baryons known to exist but hardly observed at redshift zero, and are a baryonic dark component that is additional to “dark matter”.